Development of Mandar Language Teaching Materials for Language and Cultural Preservation among High School Students in West Sulawesi - Muliastuti, Liliana; Leiliyanti, Eva; Eriyani, Reni Nur; Darmawati, Besse; Friyandini, Ratna; Ariestiara, Ajeng Rahmadania (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
Mandar, a regional language in Indonesia, is classified as "stable but threatened" according to the Language Development and Cultivation Agency (2019). This study aims to analyze the learning needs for Mandar language and develop culture-based teaching materials for high school students in West Sulawesi. Employing the Research and Development (R&D) method by Borg and Gall, this study involved 596 students, three teachers, and two school principals from 13 high schools. Results indicate that 55.8% of students exhibited high interest in learning Mandar, with preferences for listening (45.1%) and reading (37.3%) activities. Teaching materials developed through communicative and contextual approaches demonstrated effectiveness in improving vocabulary comprehension (85%), conversational skills (78%), and learning motivation (82%) during trials conducted from July 26 to August 16, 2025. Sustainable implementation requires curriculum integration, teacher training, and digital media development to ensure the preservation of Mandar language and culture.